A recurrent TP63 mutation causing EEC3 and Rapp–Hodgkin syndromes. Issue 2 (April 2016) - Brueggemann, Felix B.; Bartsch, Oliver
Abstract : The ectrodactyly, ectodermal dysplasia, and cleft lip/palate syndrome 3 (EEC3; OMIM #604292), the Rapp–Hodgkin syndrome (RHS), and various other syndromes are caused by mutations in the TP63 gene, which encodes a p53-like transcription factor. Here, we report on a woman aged 37 years and her daughter aged 3 years with the previously reported c.1028G>A (p.Arg343Gln) mutation in exon 8 of TP63 . The mother lacked ectrodactyly, indicating a diagnosis of RHS, whereas the girl presented with all three major features (ectrodactyly, ectodermal dysplasia, clefting) and different minor features (including small and brittle nails, and recurrent conjunctivitis believed to be because of stenotic and blocked nasolacrimal ducts) of the EEC3 syndrome. The EEC and EEC-like syndromes are usually distinguished on the basis of the clinical findings; however, these syndromes show a huge variability in features because of variable expressivity and incomplete penetrance, making the correct clinical assignment difficult. In EEC3 syndrome and RHS, a clustering of mutations in the different domains of TP63 can be observed. Our findings indicate the clinical variability with TP63 mutations and underline that in the case of two syndromes being clinically possible in a patient, the final diagnosis should be assigned only after molecular diagnostics.